Synthesis and Characterization of a Silica/Tungsten(VI) Oxide and Its Performance for the On-Line Solid-Phase Extraction (SPE) of Nickel Ions from Aqueous Media with Determination by Flame Atomic Absorption Spectrometry (FAAS) - Barreto, Túlio Rolim; Gorla, Felipe Augusto; Ferreira, Milena do Prado; Duarte, Pedro Henrique Araújo; Ribeiro, Emerson Schwingel [UNESP]; Afonso, Júlio Carlos; Tarley, César Ricardo Teixeira (Taylor & Francis, 2020)
The present paper describes a new analytical method exploiting a SiO2/WO3 mixed oxide as an adsorbent synthesized via sol-gel process for the preconcentration of Ni2+. This material was characterized by energy dispersive X-ray fluorescence spectroscopy, powder X-ray diffraction, Fourier transform infrared spectroscopy, analysis of the specific surface area by Brauner, Emmett and Telle multipoint method, the average pore size and pore volume by Barrett-Joyner-Halenda method, scanning electron microscopy, and electron dispersive spectroscopy. The mixed oxide presented high surface area (710.9 m2 g−1), average pore size of 35.1 Å, and average pore volume of 0.128 cm−3 g−1. This material was used as the an adsorbent in an on-line procedure for pre-concentration of solid phase extraction, based on the adsorption of Ni2+ ions at pH 10.5 followed by elution with 1.0 mol L−1 HNO3 and determination by flame atomic absorption spectrometry. Under optimized conditions, a linear range from 10.0 to 170.0 µg L−1, an enrichment factor of 38.8-fold, and limits of detection and quantification of 4.23 µg L−1 and 14.11 µg L−1 were obtained. The precision of method, estimated as percentage of relative standard deviation of ten replicates of 30.0, 90.0 and 150.0 µg L−1 Ni2+ solutions, was lower than 4.10%. The method was employed for analysis of water samples and the accuracy was attested by addiction and recovery tests, with satisfactory recoveries (98.4–109.2%). Thus, the developed material can be successfully applied to water samples for monitoring of Ni2+ at very low levels without matrix influence.
Keywords: Flame atomic absorption spectrometry (FAAS); silica/tungsten(VI) oxide; SiO2/WO3 mixed oxide; solid-phase extraction (SPE); water samples